EVALUASI PENGELOLAAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) SD NEGERI HARAPAN MAKMUR KABUPATEN MUSI RAWAS KECAMATAN MUARA LAKITAN - Yuli Nurhayati; Dondy Ekki Deonardo (Jurnal AkunStie (JAS), 2021)
The School Operational Assistance Fund (BOS) is a government program which is basically for the provision of non-personnel operating costs for basic education units as the implementer of the compulsory education program. The analytical method used is descriptive qualitative analysis method. The results show that (1) Planning for BOS funds is in accordance with the 2019 BOS Technical Guidelines because it is seen from Government Regulation Number 3 of 2019 concerning education funding from BOS funds obtained by SD Negeri Harapan Makmur which comes from the State Budget (APBN) for 2019 is IDR 157,600,000 / year, - (2) Implementation of BOS funds, especially the allocation is in accordance with the 2019 Technical Guidelines for BOS, because in the allocation, filling in dapodikdasmen data (3) the distribution of BOS funds is in accordance with the 2019 technical guidelines, namely by going through two stages (4 ) The use of BOS funds is in accordance with the 2019 Technical Guidelines for BOS, in the form of 11 components that can be funded by BOS funds. (5) not all of the supervision has been carried out due to the lack of direct supervision from the school committee (6) Reporting the accountability of BOS funds is in accordance with the 2019 Technical Guidance, only there are no banners information, and for external reports it is in accordance with the reports made every quarter.